Synthesis and characterization of hematite particles (α-Fe2O3) obtained by thermal treatment of FeSO4 with sugar - Mejia, Mirian E. (2022)
Hematite particles were synthesized by thermal treatment of FeSO4 with different concentrations of sugar. The powder mix of FeSO4 and simple sugar was held at 600 °C for 14 h in a furnace. Using ratios of 1 g and 3 g of FeSO4, to 0.1 g, 0.2 g and 0.3 g of simple sugar respectively. The analysis of the macroscopic magnetic properties of the samples was made with an alternating field magnetometer. For the structural characterization of the samples, X-ray diffractometry (XRD) and transmission Mössbauer spectroscopy (TMS) were used. Depending on the concentrations of sugar used, the presence of hematite or butlerite was observed by XRD. The sole presence of the hematite phase was observed when the ratios of 1 g of FeSO4 to 0.1 g, 0.2 g and 0.3 g of sugar were used. The hematite phase was not observed for the ratios of 3 g FeSO4 to 0.1 g, 0.2 g and 0.3 g of sugar; in these cases the  crystalline phase of butlerita (Fe(SO4)(OH)(H2O)2) was obtained. Through the Mössbauer hyperfine parameters measured by TMS, the mineralogical phase was determined by the presence of the magnetic sextet of hematite for the mixtures with 1 g of FeSO4; and in the cases of 3 g FeSO4 by the presence of two paramagnetic doublets assigned to iron cations having 3+ oxidation state. These results allowed us to correlate them with those obtained by XRD.